Constructions of Religiosity and Death Anxiety in Two Cultures: The United States and Kuwait - Thorson, James A. (Journal of psychology and theology, 1997)
Religiosity seems to moderate death anxiety, but not in all groups. The two constructs apparently are related mostly among those who are high in intrinsic religiosity or low in death anxiety, or both. Age seems to be an important factor in the development of this relationship. Samples from Kuwait (N = 294) and the United States (N = 279) completed instruments to assess death anxiety and intrinsic religious motivation. The Kuwaitis scored much higher than the Americans in both. State anxiety may have influenced the Kuwaitis’ death anxiety scores. Relationships and cross-cultural differences are examined.